Pengaruh Produk dan Loyalitas Pelanggan Terhadap Kepuasan Pelanggan Pada Kartu Indosat Di Sakha Phone Gurah - kristanti, desi; Meydiansyah, Septian Dwi; Fahira, Vicka Bella (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2020)
In this study aims to analyze the influenceof product and customer loyalty on customer satisfaction on Indosat cards in Sakha Phone Gurah.Data analysis techniques used quantitative research with the type of correlation research.The population and sample used by all customerson the Indosat Card in sakha phone Gurah 30 people.Techniques for data collection using questionnaires (primary).Data analysis techniques using multiple linear regression and hypothesis testing the F test and t test.The result of thestudy simultaneously had a significant positive effect between product and customer loyalty,this was evidenced by the significance value of  0,000,a significant level 0f 5 %.While the two loyalty variables have a greater influence compared to products with a regression value of  0.601.Thus Sakha Gurah Cellular phone especially Indosat cellular cards can pay attention to maintaining those three things forconsumers and increasing company profits.